Managing demand in the modern energy system: the role of consumers and the potential of demand response programs - Kiianchuk, Vladyslav (My University, 2023)
This article covers demand response and its potential benefits and challenges, including the roles of different consumer types and current trends and technologies. It aims to provide a comprehensive overview of the demand response landscape and its key opportunities and challenges in managing demand.
Keywords: demand response; consumers; energy management; load shifting; smart grid systems